2021
DOI: 10.1097/dcr.0000000000002113
|View full text |Cite
|
Sign up to set email alerts
|

Slow and Steady Wins the Race: A Solid Case for a 3-Stage Approach in Ulcerative Colitis

Abstract: BACKGROUND: Approximately 10% to 20% of patients with ulcerative colitis require surgery during their disease course, of which the most common is the staged restorative proctocolectomy with IPAA. OBJECTIVE: The aim was to compare the rates of anastomotic leaks among all staged restorative proctocolectomy with IPAA procedures. DESIGN: This was a retrospective cohort study. SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(58 reference statements)
2
8
0
Order By: Relevance
“…15 16 While the impact of biologic therapy on leak rates has not been clearly established, patients who are malnourished or in general poor medical condition can benefit from optimization prior to pouch construction to reduce their leak risk. 17 18 19…”
Section: Pelvic Pouch Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…15 16 While the impact of biologic therapy on leak rates has not been clearly established, patients who are malnourished or in general poor medical condition can benefit from optimization prior to pouch construction to reduce their leak risk. 17 18 19…”
Section: Pelvic Pouch Creationmentioning
confidence: 99%
“…15,16 While the impact of biologic therapy on leak rates has not been clearly established, patients who are malnourished or in general poor medical condition can benefit from optimization prior to pouch construction to reduce their leak risk. [17][18][19] Another drawback of a one-staged procedure is specifically in patients with IC, as a single-stage proctocolectomy will not allow time for pathologic determination prior to definitive pouch construction. For example, if the pathology results as CD, the patient should be informed of a higher failure rate compared to UC.…”
Section: Pelvic Pouch Creationmentioning
confidence: 99%
“…17 Additionally, the authors' experience with IPAA formation has shown that three-stage IPAA has significantly fewer anastomotic leaks and pelvic abscesses than one-stage and two-stage procedures. 18 Conversely, some studies on diverted pouches revealed that they are associated with higher rates of small bowel obstructions and more reoperations. 19,20 These obstructions may be due to obstacles with ostomy formation or with the ostomy site, such as a large body habitus that requires greater mobilization and tension to reach the abdominal wall.…”
Section: Diverted Versus Undiverted Pouchesmentioning
confidence: 99%
“…17 Additionally, the authors' experience with IPAA formation has shown that three-stage IPAA has significantly fewer anastomotic leaks and pelvic abscesses than one-stage and two-stage procedures. 18…”
Section: Diverted Versus Undiverted Pouchesmentioning
confidence: 99%
“…To the Editor-We read the article on restorative proctocolectomy by Plietz et al 1 with great interest. Although we commend the authors on their study, we cannot agree with their conclusion.…”
mentioning
confidence: 99%